The impact of national financial regulation on macroeconomic and fiscal performance after the 2007 financial shock: Econometric analyses based on cross-country data - Tobias Hagen (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
Using cross-country data, this paper estimates the impact of the 2007 financial shock on countries' macroeconomic developments conditional on national financial regulations before the crisis. For this purpose, the financial reform index developed by Abiad et al. (A New Database of Financial Reforms, 2008a) is used. The econometric analyses indicate that countries with more deregulated financial markets experienced deeper recessions, stronger employment losses, and larger government budget deficits. Against the background of the ongoing global crisis and the results of other studies, the usefulness of liberalized financial markets for macroeconomic stability and economic development should be rigorously reconsidered.
Keywords: E32; G18; C21; 330; financial crisis; financial regulation; great recession; robust regression; semiparametric regression; Finanzkrise; Schock; Finanzmarktregulierung; Wirkungsanalyse; Nichtparametrisches Verfahren; Robustes Verfahren; Welt